An Exploratory Analysis of Determining Factors Influencing Student Satisfaction with Postgraduate Program Services - Daysi Fikka Kelejan; Ronny H. Walean; Tonny Irianto Soewignyo; Deske W. Mandagi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aims to investigate the determinants influencing postgraduate student satisfaction with postgraduate program services. The study employs a combination of qualitative and quantitative methodologies. Initially, in-depth interviews were conducted with 11 actively enrolled postgraduate students, followed by a survey distributed to 90 current postgraduate students at Universitas Klabat. The collected data underwent exploratory factor analysis (EFA) using principal component analysis, facilitating the identification of factors affecting graduate student satisfaction. The findings reveal that several crucial factors significantly contribute to postgraduate student satisfaction, including institutional excellence, program enrichment, faculty characteristics, and the quality of the learning environment. The outcomes of the data analysis underscore the nuanced interplay of these elements, emphasizing their substantial influence on the satisfaction levels of students enrolled in graduate programs.